Eensaam in die Voortrekkergemeenskap: Askese en geloofsbelewing in die teologie van die Voortrekkervrou Susanna Smit (1799-1863) - Raath, A. W. G. (HTS teologiese studies, 2003)
Solitary in the Voortrekker community: Ascesis and religious experience in the theology of the Voortrekker woman Susanna Smit (1799-1863)An evaluation of Susanna Smit’s commitment to introspection, meditation and solitary contemplation necessarily has to be undertaken in the light of the major impact of the theological pietism of the Dutch Second Reformation on the Voortrekker community. Although the theological literature of the Dutch Second Reformation fundamentally influenced her views on these matters, the economic, political and ecclesiastical position in which she found herself also substantially contributed to her tendency towards solitary contemplation. The tendency to experiential ascesis is, however, not limited to the Dutch Second Reformation, and the impact of current economic and political factors on the church makes it essential, from an ecclesiastical point of view, to take note of the factors which contributed to the emphasis on mystical experiential theology. For this reason the diaries of the Voortrekker woman Susanna Smit are most illuminating and relevant.